2010
DOI: 10.3325/cmj.2010.51.165
|View full text |Cite
|
Sign up to set email alerts
|

Are Shorter Article Titles More Attractive for Citations? Cross-sectional Study of 22 Scientific Journals

Abstract: Longer titles seem to be associated with higher citation rates. This association is more pronounced for journals with high impact factors. Editors who insist on brief and concise titles should perhaps update the guidelines for authors of their journals and have more flexibility regarding the length of the title.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
67
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 5 publications
(1 reference statement)
1
67
3
1
Order By: Relevance
“…Their findings for that question have been contradictory ( [14,15] vs. [16]), suggesting a need for continued research. It is possible that discrepancies like this stem from how they compiled their title corpora, especially the decision to mix journals publishing clinical research with others focusing on bench research [15,16]. Applied linguists, in contrast, have logically looked at various surface structures besides length in the interest of informing ERPP and ESP instructors, who must teach forms (Table 2).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Their findings for that question have been contradictory ( [14,15] vs. [16]), suggesting a need for continued research. It is possible that discrepancies like this stem from how they compiled their title corpora, especially the decision to mix journals publishing clinical research with others focusing on bench research [15,16]. Applied linguists, in contrast, have logically looked at various surface structures besides length in the interest of informing ERPP and ESP instructors, who must teach forms (Table 2).…”
Section: Introductionmentioning
confidence: 94%
“…This group is particularly concerned with whether research design is included or not (Table 1). Some have also looked at other content and phrasing features potentially associated with citing, notably length [14][15][16]. Their findings for that question have been contradictory ( [14,15] vs. [16]), suggesting a need for continued research.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study on more than 9000 article from 22 different journals, authors conclude that articles in journals with higher impact factors tend to have large word counts in title and get more citations. [5] In later study, authors have chosen more variables from titles of 423 Articles divide into two separate results-describing and methods-describing titles groups. With different statistical analysis as well as logistic regression they have shown that titles with less characters would bring more citations.…”
Section: Introductionmentioning
confidence: 99%